1983
DOI: 10.1038/bjc.1983.62
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iron deficiency on experimental oral carcinogenesis in the rat

Abstract: Summary The effect of iron deficiency on oral carcinogenesis was investigated in 30 young adult male Charles River white rats. In 15 animals, prior to the start of carcinogen treatment, iron deficiency anaemia was produced and subsequently maintained by a combination of low iron diet (12mgFe2 + kg-I diet) and repeated venesection. Fifteen control animals were fed the same diet supplemented with iron to approximately 140mg Fe2+ kg-1 diet. All animals were treated with the carcinogen 0.5% 4-Nitroquinoline-N-oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Although it is not fully understood whether anemia can increase the risk of HNSCC, it has been suggested that chronic iron deficiency anemia can cause atrophy of mucosa and increase susceptibility to carcinogens. It has also been reported that the incidence of tongue tumor is increased in iron deficient animals (Prime et al, 1983). In our study 61.1% of patients with SCC of hypopharynx were anemic, compared to 41.2% of patients with SCC of the tongue and 32.9% of those with SCC of the larynx.…”
Section: Discussionmentioning
confidence: 49%
“…Although it is not fully understood whether anemia can increase the risk of HNSCC, it has been suggested that chronic iron deficiency anemia can cause atrophy of mucosa and increase susceptibility to carcinogens. It has also been reported that the incidence of tongue tumor is increased in iron deficient animals (Prime et al, 1983). In our study 61.1% of patients with SCC of hypopharynx were anemic, compared to 41.2% of patients with SCC of the tongue and 32.9% of those with SCC of the larynx.…”
Section: Discussionmentioning
confidence: 49%
“…219 I1I initiation of cancer (Willson, 1977). Iron deficiency appears to predispose to oral cancers in humans and affects the pattern of tumours induced by the carcinogen 4-nitroquinoline-N-oxide in rats (Prime et al, 1983). Several cases of primary liver cancer have been detected in iron-overloaded patients (Young & Aisen, 1982).…”
Section: Cancermentioning
confidence: 99%
“…(8) Iron has been recognized as an important element for maturation of epithelium and it is well documented that iron deficiency is associated with epithelial abnormalities in addition to malignancies like post cricoid carcinoma and tumours of the pharynx and mouth. (9) Thus biochemical alterations of copper and iron concentrations in the serum of pre malignant patients can help not only in the early diagnosis, appropriate treatment but also as an indicator for prognosis. It has been postulated that altered serum copper and iron levels are observed among OSMF patients.…”
Section: Introductionmentioning
confidence: 99%